U.S. Foreign Policy under President Trump: The Middle East, Eastern Mediterranean and Black Sea Regions - Poghosyan, Benyamin (Analytical Bulletin, 2022)
<div id=":2hr" class="Am Al editable LW-avf tS-tW tS-tY" tabindex="1" role="textbox" contenteditable="true" spellcheck="false" aria-label="Message Body" aria-multiline="true" aria-owns=":3cy" aria-controls=":3cy">The current phase in international relations can be best characterized by one word – transition. The Post-Cold War order is rapidly disappearing, creating strategic ambiguity for all actors. The U.S. hegemony is over or close to over despite the fact that militarily Washington will be safely far out of reach for several decades to come. However, the growing national debt, the looming crisis in the Social Security and Medicare systems, uncontrolled migration, growing populism and partisan fighting does not bode well for the future of U.S. dominance. At the same time, no nation, be it China, Russia, India or Brazil, has the necessary resources or will to compete for the new world hegemony. The absence of a world hegemon means that no state has the power to enforce the implementation of key international rules and norms. Regardless how one perceives the international principles – as balanced or biased – the rule-based order at least provides a minimal level of stability since the actors involved on the international stage have a clear understanding what may and may not be done. However, since the late 2000s the situation has changed. We are increasingly facing an international security architecture where key actors may easily break the norms and rules, and this will eventually bring us to a situation upon which no rules can be based. The election of President Trump sent shock waves through the United States’ political establishment and surprised international relations pundits worldwide. Despite the apparent growth of the right-wing populist movements in different parts of the world, the culmination of which was presumably the BREXIT referendum held in June 2016, few if any could imagine that a real estate developer and reality TV star had any chance of defeating one of the most respected representatives of the US political establishment. The November 2016 elections had widespread implications on both American domestic and foreign policies. President Trump’s decision to denounce globalism created a situation where the so-called “vertical globalism” (Western-led efforts to spread a liberal international order all over the world through the promotion of democracy and a market economy) might be transformed into a “horizontal globalism” based on regional integration models covering vast territories of Europe and Asia, Africa and Latin America. In this paper we will analyze President Trump’s foreign policy in several key geographical areas and its implications. However, in order to better understand the significant changes in U.S. foreign policy ushered in by President Trump and make predictions for future developments, it is worth starting with an examination of Trump’s foreign policy perceptions as well as of the ongoing debates within the foreign policy establishment itself.